Human language technology : challenges for computer science and linguistics : 7th Language and Technology Conference, LTC 2015, Poznań, Poland, November 27-29, 2015, Revised selected papers /: challenges for computer science and linguistics : 7th Language and Technology Conference, LTC 2015, Poznań, Poland, November 27-29, 2015, Revised selected papers. (2018) - Unknown
No abstract available